Field Evaluation of Container Nursery Irrigation Systems: Part 1: Measuring Operating Pressures in the Irrigation System: AE262/AE088, 1/2019 - Haman, Dorota Z.; Yeager, Thomas H. (EDIS, 2019)
Performance of sprinkler and microirrigation systems can be evaluated by measuring operating pressures, application rates, and uniformity of water application under nursery conditions. Knowledge of these factors is important to determine the causes of poor system performance. This publication will focus on operating pressure and will discuss application rates and uniformity in other publications.